PENGARUH STARTEGI PEMBELAJARAN AKTIF TIPE PENCARIAN INFORMASI TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 SUTERA KABUPATEN PESISIR SELATAN - Nursanti, Dora; Rismen, Sefna; lovia, Lita (Pendidikan Matematika, 2014)
ABSTRACT The background of this research is about students understanding of mathematical concepts is still low. The aims of this research is to know the students understanding of mathematical concepts by strategis to find the information is better than the students understanding of mathematical concepts by strategis the information conventional learning in VIII grade SMPN 4 Sutera. The kind of this research is experimental research by random design towards the subject. The population in this research was students in VIII grade SMPN 4 Sutera in school year 2013/2014. The sample Class were chosen is VIII.4 class as experimental class and VIII.2 class as control class . The instrument which was used is final test which is essay  from with reliability is  0.7403. Based on calculations of data analysis using t-test of the side obtained = 2.29 and = 1.645 . So  >  thus it can be concluded that students understanding of mathematical concepts apply strategies the information is better than the students understanding of mathematical concepts by applying conventional learning in VIII SMPN 4 Sutera.